Phenotypic plasticity in locomotor performance of a monophyletic group of weevils accords with the 'warmer is better hypothesis - Treasure, Anne M.; Chown, Steven L. (Journal of Experimental Biology, 2019)
Ectotherms may respond to variable environmental conditions by altering their phenotypes. Phenotypic plasticity was initially thought to be beneficial to an organism's physiological fitness but several alternative hypotheses have been proposed with growing empirical support. In this study, we tested the full suite of hypotheses by investigating acclimation responses of locomotor performance for nine populations of five species of sub-Antarctic weevils, using static and fluctuating temperatures. Species showed typical locomotion thermal performance curves with temperature of the maximum speed ( T opt ) ranging between 22.3±1.7°C (mean±s.e.m.) and 31.1±0.7°C. For most species, T opt was not affected by acclimation. For maximum speed ( U max ), significant, positive effects of acclimation were found for all species except a supralittoral one. Individuals acclimated to 0°C showed much lower values than the other two acclimation treatments (15°C and fluctuating 0–15°C). Performance breadth (the index of the breadth of the curve, T br ) typically showed little response to acclimation. None of the traits of the supralittoral species was affected by acclimation treatment. Responses to stable and fluctuating temperature treatments were similar. Our findings also revealed that the mean estimated activation energy 0.40±0.015 eV (mean±s.e.m.) was lower than for other herbivores, the category to which these weevils belong, suggesting that some form of compensation in the rate–temperature relationship may be evident. Thus, we typically found support for the ‘warmer is better’ hypothesis for acclimation of locomotor performance, although some compensation was evident.